Sosialisasi Digitalisasi UMKM dan Pendampingan Pembuatan Google Maps Di Desa Sei Rejo Kecamatan Sei Rampah - Dea Ananda; Vira Septria; Nabila Marsya Sitompul; Nursacharissa Devitasari; Mhd Ariel Pranata; Sriwardany Sriwardany (Journal Of Human And Education (JAHE), 2026)
The utilization of digital technology by Micro, Small, and Medium Enterprises (MSMEs) in Sei Rejo Village remains suboptimal, particularly in the use of Google Maps as a medium for providing business location information. This community service activity aimed to improve MSME owners’ understanding of the importance of business digitalization through socialization and assistance in creating Google Maps listings. The activity was carried out through observation, socialization with several MSME owners, discussions, and assistance in registering a business location on Google Maps for one participating MSME. The results showed an improvement in participants’ understanding of the benefits of business digitalization, as well as the successful registration of one MSME’s business location on Google Maps. This activity is expected to encourage MSME owners to utilize digital technology to expand access to information about their businesses